(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
Malay architecture has undergone modifications due to cultural influences and development in its composition. Local architecture is established through natural elements and constructed based on the wisdom of the Malay mind. The relationship between the architecture and the Malay mind is reflected in the proverbs of the Malay community. Accordingly, this study attempts to examine the Malay proverbs pertaining to the architectural structure of the Malay house within the framework of semantic theory. The relevant data were generated from the Pusat Rujukan Persuratan Melayu Data Base at Dewan Bahasa dan Pustaka (http://www.prpm.dbp.gov.my/). A total of 63 proverbs relating to natural objects of house architecture was collected. However, this study only analyzes and describes the material object "stair" because its occurrence is the highest in the data along with its unique function. The analysis is couched in the Great Chain of Being Metaphor and specific Metonymy that stands for the generic for describing cognitive mapping from the concrete source domain to the abstract target domain. Subsequently, the inquisitive semantic approach explains the justifications of selecting the relevant objects, and explicates the reflection of the Malay mind. The findings demonstrate the existence of human characteristics, such as status, realistic attitude, and dignity which are exemplified by the material object "stair". The importance of stairs from various aspects, such as construction, material, components and culture, successfully reflect the Malay mind. This cross-disciplinary study is a successful innovation in the study of linguistics and Malay architecture. Keywords: inquisitive semantics, architectural structure, material object, Malay proverbs